The Relationship Between Regional Autonomy and Bureaucratic Performance: A Social Study on the Effectiveness of Local Government - Suripto, Suripto (PT. Anagata Sembagi Education, 2025)
Regional autonomy is a key instrument for strengthening local government effectiveness, yet its impact largely depends on bureaucratic capacity and the quality of state–society relations. This study analyzes how the structure of regional autonomy, institutional capacity, and local socio-political dynamics influence the performance of local governments in Indonesia. Using a qualitative method through a literature-based policy analysis, the study systematically reviews relevant international and national research as well as official reports from organizations such as the OECD, the Ministry of Administrative Reform, and the World Bank. The findings show that autonomy does not automatically improve local service delivery, as variations in bureaucratic capacity including human resource competence, leadership quality, organizational culture, and innovation capability, constitute the primary determinants of governance effectiveness. Furthermore, weak public participation, limited transparency, and inadequate social accountability hinder the realization of the potential benefits of decentralization. These results highlight that effective local governance emerges from the interaction of delegated authority, strong bureaucratic capacity, and democratic state–society relations. The study recommends strengthening civil service capacity, improving accountability mechanisms, and advancing governance reforms to ensure that regional autonomy fulfills its intended purpose and contributes to societal welfare.